2020
DOI: 10.1172/jci.insight.134251
|View full text |Cite
|
Sign up to set email alerts
|

Siponimod enriches regulatory T and B lymphocytes in secondary progressive multiple sclerosis

Abstract: 5 The AMS04 Study Group is detailed in the Supplemental Acknowledgments. BACKGROUND. Siponimod (BAF312) is a selective sphingosine-1-phosphate receptor 1 and 5 (S1PR1, S1PR5) modulator recently approved for active secondary progressive multiple sclerosis (SPMS). The immunomodulatory effects of siponimod in SPMS have not been previously described. METHODS. We conducted a multicentered, randomized, double-blind, placebo-controlled AMS04 mechanistic study with 36 SPMS participants enrolled in the EXPAND trial. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…In addition, S1P acting at S1PR 1 inhibits the function of regulatory T cells, by blocking the differentiation of precursor cells and the function of mature cells, and so reduces their suppression of Th17 formation [89]. Interestingly, immunophenotyping analyses have shown that fingolimod and siponimod induce a reduction in circulating CD4+ T cells, CD8+ T cells (specifically a selective reduction of naïve and central memory T cells with a relative increase of peripheral effector memory T cells), as well as B cells, in patients with RRMS and SPMS, respectively [90][91][92]. Gene expression studies have also shown reductions in the expression of key inflammation-related genes with fingolimod in patients with RRMS [93] and with siponimod in patients with SPMS [91].…”
Section: S1pr Modulation and Effects On Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, S1P acting at S1PR 1 inhibits the function of regulatory T cells, by blocking the differentiation of precursor cells and the function of mature cells, and so reduces their suppression of Th17 formation [89]. Interestingly, immunophenotyping analyses have shown that fingolimod and siponimod induce a reduction in circulating CD4+ T cells, CD8+ T cells (specifically a selective reduction of naïve and central memory T cells with a relative increase of peripheral effector memory T cells), as well as B cells, in patients with RRMS and SPMS, respectively [90][91][92]. Gene expression studies have also shown reductions in the expression of key inflammation-related genes with fingolimod in patients with RRMS [93] and with siponimod in patients with SPMS [91].…”
Section: S1pr Modulation and Effects On Lymphocytesmentioning
confidence: 99%
“…Interestingly, immunophenotyping analyses have shown that fingolimod and siponimod induce a reduction in circulating CD4+ T cells, CD8+ T cells (specifically a selective reduction of naïve and central memory T cells with a relative increase of peripheral effector memory T cells), as well as B cells, in patients with RRMS and SPMS, respectively [90][91][92]. Gene expression studies have also shown reductions in the expression of key inflammation-related genes with fingolimod in patients with RRMS [93] and with siponimod in patients with SPMS [91]. Additionally, siponimod was shown to shift the immune system toward an anti-inflammatory and suppressive homeostatic state through enrichment of regulatory T cells, transitional regulatory B cells and B1 subsets, possibly contributing to the clinical efficacy of siponimod in SPMS [91].…”
Section: S1pr Modulation and Effects On Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Siponimod, a direct successor of fingolimod for oral use with a similar mode of action was recently approved for the treatment of adults with secondary progressive MS with active disease evidenced by relapses or imaging features of inflammatory activity [ 81 ]. A recent study showed that siponimod reduces the total lymphocyte and B cell count, while increasing the proportion of regulatory B cells and decreasing the frequency of memory B cells [ 82 ]. In a murine myasthenia gravis model, no change was observed in either antibody titers or total or antigen-specific plasma cell populations after treatment [ 83 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%
“…In SPMS patients, RNA derived from whole-blood samples of siponimod-treated patients have reduced expression levels of immune-associated genes involved in T-and B-cell activation and receptor signaling, which is consistent with the reduction in CD4+ T cells, CD8+ T cells, and B cells. Flow cytometric analyses showed that, within the remaining lymphocyte subsets, the incidences of CD4 + and CD8 + naive T cells were reduced, while anti-inflammatory Th2 and T regulatory cells (Tregs) were enriched [120], indicating a shift towards an anti-inflammatory and suppressive homeostatic immune system that can contribute to the clinical effectiveness of siponimod in SPMS.…”
Section: From Fty720 To Siponimodmentioning
confidence: 99%